Asiaticoside increases aquaporin-3 protein expression in the cytoplasm of normal human epidermal keratinocytes - Wijayadi, Linda Yulianti; Darmawan, Hari (Faculty of Medicine, Trisakti University, 2017)
IntroductionSkin hydration decreases with aging. Aquaporin-3 (AQP3) is a major protein that plays a role in skin hydration, therefore it is a novel target for skin moisturizing treatment. Retinoic acid (RA) as a well-known active agent in antiaging treatment increases AQP3 expression, but frequently causes harmful side effects. Asiaticoside, a saponin compound isolated from Centella asiatica (CA) is also known as an antiaging cosmetic and plays a role in wound healing. The aim of this study was to evaluate and compare the effect of asiaticoside isolated from CA and the effect of RA on the AQP3 expression in normal human epidermal keratinocytes (NHEKs).Methods An experimental laboratory study was performed using primary NHEKs that were derived from the foreskin of a boy. AQP3 expression in NHEKs was examined in vitro after the cells were incubated for 24 hours with asiaticoside or with RA at several concentrations. The AQP3 expression was evaluated by immunocytochemistry and quantitatively analyzed by Image-J software. Independent t-test and one-way ANOVA were used to analyze the data, followed by post-hoc Tukey test.ResultsThere was an increasing trend of AQP3 expression upon exposure to asiaticoside at all concentrations compared to the control group. However, RA exposure seemed to induce a higher level of AQP3 expression. Asiaticoside effected a lower increase in AQP3 expression in NHEKs than did RA (p=0.042). Optimal results were achieved at 1 mg/mL concentration of asiaticoside.ConclusionsAsiaticoside isolated from CA can enhance the AQP3 expression in NHEKs. Therefore it can be used as an active ingredient in cosmetic moisturizer formulation for dry skin treatment.